1991
DOI: 10.1177/001872089103300502
|View full text |Cite
|
Sign up to set email alerts
|

The Older Driver

Abstract: Older drivers constitute the most rapidly growing segment of the driving population in number of drivers licensed, miles driven, and proportion of the driving population. Yet the highway transportation system has not been designed for these drivers. This lack of fit is reflected in the accelerating rate of crashes per mile driven experienced by older drivers beginning around age 55. Furthermore, older persons are more vulnerable to injury once a crash occurs and as a group experience a higher fatality rate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(46 citation statements)
references
References 4 publications
1
44
0
1
Order By: Relevance
“…Since it is of primary importance to meet the mobility needs of this growing population of older adults (Ball, 1997), society has to find a way to differentiate those old drivers who may pose a threat to their own or other road users safety, from those people who are safe drivers. Conventional medical examination for licence renewal is recognised to be of limited value in assessing full range of 'on the road' ability, as well as stressful to older drivers (Waller, 1991;Adler, 1997;Carr et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since it is of primary importance to meet the mobility needs of this growing population of older adults (Ball, 1997), society has to find a way to differentiate those old drivers who may pose a threat to their own or other road users safety, from those people who are safe drivers. Conventional medical examination for licence renewal is recognised to be of limited value in assessing full range of 'on the road' ability, as well as stressful to older drivers (Waller, 1991;Adler, 1997;Carr et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lo mismo ocurre en el caso de los conductores mayores, es decir los que superan los 70 años de edad [15][16][17] .…”
Section: Discussionunclassified
“…Poor cognitive functions can affect safe driving in several ways, including when a person is engaging in unsafe self-regulated driving, has difficulty in navigating and gets lost, and responds appropriately to quickly changing traffic information (Eby and Molnar, 2012). However, many people begin to adjust their driving as they age: research has shown that elder drivers strategically avoid dangerous driving situations, such as night driving, poor weather, and periods of peak traffic, and they drive more carefully so that they can compensate for their declined sensory, cognitive, and motor functions (Waller, 1991;Rudi and Ingrid, 2000). While many see self-regulation as a success in promoting safety, it could result in lost mobility.…”
Section: Age-related Changes In Cognitive Functionmentioning
confidence: 99%